What do people think of forestry - a student opinion survey - Manikam, Doraisingam; Sastry, Cherla B.; Abdul Jamil, Hussein; Ahmad, Abdul Manap (Forestry Department Peninsular Malaysia, 1978)
A survey was conducted among the students of the University Per- tanian Malaysia to assess their opinion about the forestry profession in general and Malaysian forestry in particular. A detailed questionnaire was prepared for this purpose. One hundred and fifty students responded to this questionnaire. For obvious reasons, forestry students were excluded from this survey. The study was conducted in two parts namely, an initial pilot study and a subsequent detailed survey. Both systematic and random sampling techniques were used and the data were analysed statistically. The present survey indicates that student opinion about forestry, although favourable. is based on inadequate knowledge. Thus, there is a definite need for more extension work to publicise the role of forestry in the national development.